2018
DOI: 10.21475/ajcs.18.12.04.pne835
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-physiological adaptation of Jatropha curcas L. to salinity stress

Abstract: The aim of the current study is to assess the growth response, biochemical changes, photosynthetic pigments content and gas exchanges of physic nut (Jatropha curcas) grown under natural saline conditions. The experiment was arranged in a completely randomized design based on the following soil electrical conductivities: 0.29 dS.m -1 (control), 1.76 dS.m -1 (moderate salt concentration), 2.61 dS.m -1 (high salt concentration), 3.79 dS.m -1 (very high salt concentration). Physic nut plants were kept under saline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 48 publications
2
8
1
Order By: Relevance
“…Bhargava et al (2014) and Sixto et al (2016), in working with Eucalyptus under salt stress, observed that the salinity promoted the reduction of gas exchange in plants. In a similar way, studies done with Anacardium occidental (Bezerra et al, 2003), Ricinus communis L. (Pinheiro et al, 2008), and Jatropha curcas L. (Cavalcante et al, 2018) cultivated in saline soil have also confirmed that gas exchanges are negatively affected by salinity, as observed among Eucalyptus clones.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…Bhargava et al (2014) and Sixto et al (2016), in working with Eucalyptus under salt stress, observed that the salinity promoted the reduction of gas exchange in plants. In a similar way, studies done with Anacardium occidental (Bezerra et al, 2003), Ricinus communis L. (Pinheiro et al, 2008), and Jatropha curcas L. (Cavalcante et al, 2018) cultivated in saline soil have also confirmed that gas exchanges are negatively affected by salinity, as observed among Eucalyptus clones.…”
Section: Discussionsupporting
confidence: 57%
“…Reductions in gas exchange, caused by salt stress, contributed to reduction in biomass production, which can be confirmed by the correlations of gs, A and A/Ci with the TDM, in the largest salt concentrations. Indeed, biomass production is reduced as a consequence of less CO 2 assimilation, as has been verified also in Eucalyptus plants (Sixto et al 2016) and in Jatropha curcas L. (Cavalcante et al 2018) under salt stress.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Passion fruit is highly sensitive to salinity (Dias et al 2011), which affects the plant photosynthetic apparatus. This effect can be interpreted by the maximum quantum efficiency of the photosystem II, through the Fv/Fm ratio, or by damage to photosynthetic pigments, assessed via the chlorophyll content (SPAD) index (Freire et al 2014), thus decreasing seedling growth and dry weight yield (Bezerra et al 2016, Cavalcante et al 2018.…”
Section: Palavras-chavementioning
confidence: 99%